The Determinants of Full‐Time versus Part‐Time Reemployment following Job Displacement - McCall, Brian P. (Journal of Labor Economics, 1997)
This article explores the determinants of full‐time and part‐time reemployment following job displacement in Canada. Among those who lose full‐time jobs, women are found to have both longer median joblessness durations and higher probabilities of part‐time reemployment than men with little of this difference explained by gender differences in worker characteristics. Unemployment insurance receipt is associated with longer median joblesness durations and, among those who find a job within 1 year of displacement, an increased probability of part‐time reemployment for both men and women.